Proceedings of the 36th IEEE Conference on Decision and Control
DOI: 10.1109/cdc.1997.649756
|View full text |Cite
|
Sign up to set email alerts
|

Study of design directions for lateral vehicle control

Abstract: Lateral vehicle control for passenger cars, a vital control subsystem of Automated Highway Systems (AHS), has been studied for several decades. Different reference systems have been examined for detecting the lateral vehicle displacement from the lane center. Implementations of 'look-down' reference systems, however, encountered practical constraints, limiting driving speed to approximately 20 m/s under realistic conditions. This paper presents new perspectives on design directions for lateral vehicle controll… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
0

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(18 citation statements)
references
References 8 publications
0
18
0
Order By: Relevance
“…This tradeoff offers some advantages, as mentioned before, such as faster planning and simpler, easierto-maintain planning algorithms. We are primarily concerned with low-speed path tracking in this paper, although there has been considerable work on high speed vehicle control, such as [8], [9], [10], [11]. However, dynamic effects don't need to be included for low-speed vehicles, as evidenced by some recent papers [12], [13].…”
Section: Related Workmentioning
confidence: 93%
“…This tradeoff offers some advantages, as mentioned before, such as faster planning and simpler, easierto-maintain planning algorithms. We are primarily concerned with low-speed path tracking in this paper, although there has been considerable work on high speed vehicle control, such as [8], [9], [10], [11]. However, dynamic effects don't need to be included for low-speed vehicles, as evidenced by some recent papers [12], [13].…”
Section: Related Workmentioning
confidence: 93%
“…The complete model combining vehicle model (1) and vision dynamics (2) and (3) is represented in state space form as below:…”
Section: Equations Of Motionmentioning
confidence: 99%
“…The lateral sensing system consists of magnetic markers embedded along the road centerline every 1.2 meter and two sets of magnetometers installed under the vehicle's front and rear bumpers [3] [10]. Experiments have shown that the "look-ahead" scheme utilizing these two sets of magnetometers' outputs results in good control performance [3]. It has also been shown, however, that the performance of the scheme is sensitive to failures of the magnetometers [10].…”
Section: Introductionmentioning
confidence: 99%
“…For example, the value of 0 is chosen such that 99% of the measurement noise is within the range (-0.02 0.02). We set 3,0 =0.003, 3,3 =0.995 and 3,4 =0.002 because the sensing system in failure mode 3 (the rear set of magnetometers suffers from failure F1) at step k is much more likely to stay at mode 3 at step k+1. It's also possible for it to jump to mode 0 (the magnetometer works again) or to mode 4 (the rear set of magnetometers suffers from failure F2).…”
Section: Simulationmentioning
confidence: 99%
See 1 more Smart Citation